Evaluation and comparison of efficacy of three desensitizing dentifrices on dentinal hypersensitivity and salivary biochemical characteristics: A randomized controlled trial - Deepthi Athuluru; Chandrasekhara Reddy; K M Sudhir; Krishna Kumar; Sreenivasulu Gomasani; Sreenivas Nagarakanti (Dental Research Journal, 2017)
Background: This study aimed to evaluate and compare the efficacy of three desensitizing dentifrices on dentinal hypersensitivity (DH) and salivary biochemical characteristics. Materials and Methods: A randomized, parallel arm, triple-blinded, clinical trial was conducted over a period of 12 weeks, with a total of three visits: baseline, 6 weeks, and 12 weeks. Calcium sodium phosphosilicate, potassium nitrate and amine fluoride dentifrices were compared. A total of 68 subjects who satisfied the inclusion criteria were included and randomly divided into four groups. Visual analog scale scores for controlled air stimulus were used to assess dentinal sensitivity and salivary pH and buffering capacity were recorded at baseline, 6 and 12 weeks. Results: All groups showed a reduction in sensitivity scores at 6 and 12 weeks. The calcium sodium phosphosilicate group showed a higher degree of effectiveness in reducing DH than potassium nitrate, amine fluoride dentifrices, and placebo for sensitivity measures. Salivary pH of calcium sodium phosphosilicate group was more toward neutral, and the buffering capacity of the same group showed significant changes from baseline to 6 and 12 weeks compared to the other groups. Conclusion: The desensitizing toothpaste containing calcium sodium phosphosilicate was found to be more effective in reducing DH and showed improvement in salivary biochemical characteristics over a period of 12 weeks compared to others.